Pre-clinical evaluation of rHDL encapsulated retinoids for the treatment of Neuroblastoma - Nirupama eSabnis; Suraj ePratap; Paul eBowman; Irina eAkopova; Andras G Lacko (Frontiers Media S.A., 2013)
Despite major advances in pediatric cancer research, there has been only modest progress in the survival of children with high risk neuroblastoma (HRNB). The long term survival rates of HRNB in the United States are still only 30-50%. Due to resistance that often develops during therapy, development of new effective strategies is essential to improve the survival and overcome the tendency of HRNB patients to relapse subsequent to initial treatment. Current chemotherapy regimens also have a serious limitation due to off target toxicity. In the present work, we evaluated the potential application of reconstituted high density lipoprotein (rHDL) containing fenretinide (FR) nanoparticles as a novel approach to current neuroblastoma therapeutics. The characterization and stability studies of rHDL-FR nanoparticles showed small size (<40nm) and high encapsulation efficiency. The cytotoxicity studies of free FR vs. rHDL/ FR towards the neuroblastoma cell lines SK-N-SH and SMS-KCNR showed 2.8 and 2 fold lower IC50 values for the rHDL encapsulated FR vs. free FR. More importantly, the IC50 value for retinal pigment epithelial cells (ARPE-19), a recipient of off target toxicity during FR therapy, was over 40 times higher for the rHDL/ FR as compared to that of free FR. The overall improvement in in vitro selective therapeutic efficiency was thus about 100 fold upon encapsulation of the drug into the rHDL nanoparticles. These studies support the potential value of this novel drug delivery platform for treating pediatric cancers in general, and neuroblastoma in particular